Collaborative conservation of cave-roosting bats: guidance on managing rock climbing near caves - Schorr, Robert A.; Warren, Zachary A.; Goodwin, Katie; Murdock, Erik; Neubaum, Daniel J. (Frontiers in Conservation Science, 2025)
Bats in North America have undergone unprecedented declines from various threats, including energy development, habitat loss, and disease. Mitigating these threats requires targeted conservation measures that address bat habitat and roosting requirements. One roosting structure commonly used by bats is caves. Human visitation to caves may cause disturbance to roosting bats through changes in noise, airflow, and temperature. Recreational climbing that occurs in and around caves may create vectors for disease transmission, disrupt bat roosting and physiology, and compromise bat conservation. However, managing certain climbing activities, such as climbing within caves and cave openings, and prolonged route development around cave openings, can ensure coexistence of recreational climbing and bat conservation. We outline bat biology at caves, potential stresses and threats to bats, and methods of managing climbing activity to conserve bats. In particular, we recommend limiting climbing activities within cave openings, and taking precautions to minimize disturbance based on distance from the cave opening. Finally, we advocate for collaboration between the climbing community and biologists to study and understand climbing impacts to bats.